Mapeamento da vegetação urbana e distribuição espacial e temporal de ilhas de calor - Oliveira, Felício Santos de (2015)
The urban sprawl and the illegal occupation of land hinder the implementation of appropriate plans that enable the integration of the built and vegetated areas, causing decreased quality of life in cities. The transformation of the soil surfaces are responsible for profound changes in the energy balance, causing, among other consequences, influence the dynamics of air movement, temperature increase in the cities and the phenomenon of urban heat island. The set of vegetation in urban environments contributes to the improvement of environmental quality and maintain ecological balance. In this context, this paper aims to map and identify urban vegetation of the city of Vila Velha, located in the metropolitan region of Greater Vitória, and analyze the benefits provided by, especially in relation to the effect on the urban heat island. The work was divided into the following methodological steps: a) mapping of urban vegetation by photo-interpretation on screen; b) identification and spatial distribution of green áreas; c) calculation of environmental quality indices; d) application of an algorithm and remote sensing techniques to obtain the distribution of surface temperature; f) ecological assessment of Vila Velha urban heat island on 16 dates between the years 2008 and 2011. The results met 20.86 km² of urban vegetation distributed in 16 classes, 42 open spaces and 09 green areas in the city and a Green Area Index (GAI) of 17.56 m²/habitant. It is yet obtained a positive correlation coefficient between the values of land surface temperature (LST) and Normalized Difference Built-up Areas Index (NDBI), was observed and recorded at least an increase of 2.34 °C urbanized areas relative to its surroundings not urbanized.